1967
DOI: 10.1126/science.156.3776.821
|View full text |Cite
|
Sign up to set email alerts
|

DDT Residues in an East Coast Estuary: A Case of Biological Concentration of a Persistent Insecticide

Abstract: DDT residues in the soil of an extensive salt marsh on the south shore of Long Island averaged more than 13 pounds per acre (15 kilograms per hectare); the maximum was 32 pounds per acre (36 kilograms per hectare). A systematic sampling of various organisms from the vicinity showed concentrations of DDT increasing with trophic level through more than three orders of magnitude from 0.04 part per million in plankton to 75 parts per million in a ring-billed gull. Highest concentrations occurred in scavenging and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
4

Year Published

1970
1970
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(45 citation statements)
references
References 41 publications
(16 reference statements)
0
41
0
4
Order By: Relevance
“…A 1967 study found that DDT levels were 20,000 times higher in one fish species than they were in the surrounding sea water, and 520,000 times higher in fish-eating cormorants (90). So, when humans eat foods higher on the food chain (more meat, milk, cheese, and eggs and fewer plant foods), they increase their exposure to bioaccumulated pesticides.…”
Section: Pesticides and Healthmentioning
confidence: 99%
“…A 1967 study found that DDT levels were 20,000 times higher in one fish species than they were in the surrounding sea water, and 520,000 times higher in fish-eating cormorants (90). So, when humans eat foods higher on the food chain (more meat, milk, cheese, and eggs and fewer plant foods), they increase their exposure to bioaccumulated pesticides.…”
Section: Pesticides and Healthmentioning
confidence: 99%
“…Zerstörung der Ozonschicht [214] Polychlorierte Biphenyle [215,216] > 20 Anreicherung in der Nahrungskette [217,218] DDT [b] > 20 Anreicherung in der Nahrungskette; [217,219] verminderte Fruchtbarkeit bei Vögeln [220] Plastik (PE, PP)…”
Section: Lebensdauer In Jahrenunclassified
“…WOODWELL et al (1967) have shown that there is usually an increase in concentration of DDT residues from smaller to larger organisms and from lower to higher trophic levels.…”
Section: Discussionmentioning
confidence: 99%